Reproductibilité du système métabolique Fitmate™ Cosmed pour mesurer la dépense énergétique sous maximale du pédalage - Louis, J.; Hausswirth, C.; Brisswalter, J. (Science & Sports, 2012)
Introduction: The purpose of this study was to test the reproducibility of the Fitmate™ metabolic system in measuring breathing gas during a cycling exercise. Synthesis of the facts: Twenty-one participants performed during two sessions three 5-min exercises at submaximal intensities (16, 18 et 21 km/h). The reproducibility of respiratory variables was assessed between the two sessions. Results: Intraclass correlation coefficient (ICC) between the two sessions and for all intensities ranged from 0.61 to 0.71 for VO2 and from 0.79 to 0.89 for VE. Coefficient of variation CV are always lower than 10% for all parameters and all speeds. These results indicate a good reproducibility for VE and a satisfactory reproducibility for VO2 and cycling efficiency. Conclusion: The Fitmate™ portable metabolic analyzer provides reproducible measures of VO2 and VE during steady-state exercise that allows the assessment of energy expenditure in a simple manner in a clinical framework.